Micro-Blog Recommendation Based on User Interests and Recommendation Trust Domain - Yabin Xu; Chao Liu; Zhuang Wu (Dianxin kexue)
Recommending micro-blogs to users whom are interested in is an important way to improve the user's experience. In order to make the recommended micro-blog more match user's interests and tastes, a micro-blog recommendation method was proposed. The method considers not only user's own characteristics, but also the evaluation from the user's community. In technology, vector machine（SVM）was supported for text classification to discover user interests, and through multidimensional Newman algorithm to discover user's community. This community will be regarded as the recommendation trust domain. Finally, the improved collaborative filtering algorithm was used. It integrated user's interests and recommendation trust domain to recommend micro-blog, in order to improve the quality of micro-blog recommendation. The experimental results show that, the micro-blog recommendation method is practical and effective.